Glioblastoma multiforme in conus medullaris with intracranial metastasis after postoperative adjuvant therapy. Issue 13 (March 2017) - Yan, Chengrui; Kong, Xiangyi; Yin, Hua; Wang, Yu; He, Huayu; Zhang, Hui; Gao, Jun; Li, Yongning; Ma, Wenbin
Abstract : Abstract: Spinal glioblastoma multiforme is not common among spinal cord tumors. According to our literature review, only 27 cases originating from the conus medullaris were reported. We herein reported a case of a 10-year-old child diagnosed with glioblastoma multiforme. The patient received adjuvant radiotherapy and standard temozolomide chemotherapy after total excision. Intracranial lesions were found 1 month after postoperative adjuvant therapy. We described the clinical characteristics and postoperative therapy of the patient, and reviewed all of the published cases of conus medullaris glioblastoma. Location, age, leptomeningeal spread, and secondary hydrocephalus may be predictive factors. Immunohistochemical factors such as p53 and Ki-67 are also important. Combined treatment of surgery and postoperative adjuvant therapy is commonly used, but is controversial.